A new genus and species of micro bee flies from Brazil (Diptera: Mythicomyiidae: Psiloderoidinae) - Lamas, Carlos J. E.; Falaschi, Rafaela L.; Evenhuis, Neal L. (Zootaxa, 2015)
A new genus of Mythicomyiidae, Amydrostylus triadicophallus gen. nov. et sp. nov., is described from the Chaco of Mato Grosso do Sul, Brazil. The type-series was collected by Malaise traps during the development of the SISBIOTA–Brasil project. Amydrostylus is closely related to the genus Acridophagus Evenhuis in the subfamily Psiloderoidinae, but it is distinguished by the minute apical stylus and the same length of br and bm cells. The species is described and illustrated in detail, including the male terminalia and female spermathecae. This is the first record of the subfamily Psiloderoidinae in South America.